KEBIJAKAN SANKSI AMERIKA SERIKAT TERHADAP RUSIA ATAS ANEKSASI CRIMEA TAHUN 2014 - Citra Riaswati (HI 16 UMY 103, 2016)
*103 This article tries to explain the policy of The US gave economic sanctions against Russia after Crimea was being annexed by Russia in 2014. The US and the EU started giving economic sanctions in March 2014 and so far sanctions have been the most effective instrument of Western influence on Russia’s policy towards Ukraine, stopping Russia from making a greater military incursion in the country. Restrictions were imposed against more than one hundred members of the Russian political and business elite, as well as dozens of Russian enterprises and banks. Threrefore, US uses its sanctions as it is the only way to influence Russia’s policy towards Ukraine in the short- and mid-term, and will not be lifted its sanctions until Russia respects Ukraine’s integrity and sovereignty. Keywords: United States Policy, European Union, Russia, Sanction, Annexation of Crimea